Recall Rates of Patients in Endodontic Treatments: A Critical Review - Marques Paes da Silva, Alexandre; Barbosa Lopes, Cristiane; Vaz de Azevedo, KÃ¡tia Regina; Teixeira de Lima Ribeiro Andrade, Rosana Helena; Vidal, Fabio; de Souza GonÃ§alves, Lucio; Marques Ferreira, Manuel; de Carvalho Ferreira, Dennis (Iranian Endodontic Journal, 2019)
The number of patients that return for recall appointments has great importance to validate endodontic treatment outcomes. The purpose of this review was to investigate the rate of return on recall and the main factors that influence this rate of return. A literature review was performed in the PubMed database for the years from 1978 to 2017, using the following keywords: recall rate, endodontic treatment, endodontic retreatment, apical surgery. The inclusion criteria were: prospective studies in English, and in vivo research with humans, which included patient return rates. A total of 35 studies that fulfilled the established criteria were selected. The percentage of patients who returned on recall was 56%. More female patients (60%) attended the recall appointments than male (40%). The three main reasons for not returning were: patients did not observe the follow-up appointment (490), not returning due to a lack of interest (99) and changing their address (222). The age of the patients attending the appointments varied from 28.6 to 62 years old, with the highest percentage of patients that returned ranging from 40 to 52.5 years old. According to the literature the optimal rate of return for follow-up treatment should be greater than 80%, for the validity of the research. However, the reality presented in the studies is far from ideal. Many studies do not even mention these rates of return in their methodologies or in their results, which may mask the true treatment success rates. Keywords: Endodontic Recall; Follow-up; Recall